2006
DOI: 10.1029/2005ja011447
|View full text |Cite
|
Sign up to set email alerts
|

Differences between CME‐driven storms and CIR‐driven storms

Abstract: [1] Twenty one differences between CME-driven geomagnetic storms and CIR-driven geomagnetic storms are tabulated. (CME-driven includes driving by CME sheaths, by magnetic clouds, and by ejecta; CIR-driven includes driving by the associated recurring high-speed streams.) These differences involve the bow shock, the magnetosheath, the radiation belts, the ring current, the aurora, the Earth's plasma sheet, magnetospheric convection, ULF pulsations, spacecraft charging in the magnetosphere, and the saturation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
567
2
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(600 citation statements)
references
References 122 publications
25
567
2
6
Order By: Relevance
“…As has been shown in numerous works [see, e.g., Lorentzen et al, 2002;Tverskaya et al, 2003;Obara and Li, 2003;Hudson et al, 2004;Looper et al, 2005;Borovsky and Denton, 2006, and references therein], the interplanetary shocks and pressure jumps in the solar wind can result in the compression of magnetosphere, the formation of new ion and electron radiation belts, and the generation of magnetic storms. Both Sheath and CIR are characterized by high pressure and can have the shock in front of them and, therefore, they can compress magnetosphere and generate storms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As has been shown in numerous works [see, e.g., Lorentzen et al, 2002;Tverskaya et al, 2003;Obara and Li, 2003;Hudson et al, 2004;Looper et al, 2005;Borovsky and Denton, 2006, and references therein], the interplanetary shocks and pressure jumps in the solar wind can result in the compression of magnetosphere, the formation of new ion and electron radiation belts, and the generation of magnetic storms. Both Sheath and CIR are characterized by high pressure and can have the shock in front of them and, therefore, they can compress magnetosphere and generate storms.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Wang et al [2003] found that a southward field component Bz ≤ −3 nT with a duration of Δt ≥ 1 h results in moderate magnetic storms (Dst min ≤ −50 nT) and threshold values of Bz ≤ −6 nT with a duration of Δt ≥ 2 h result in strong magnetic storms (Dst min ≤ −100 nT), and these results differ somewhat from the results of previous papers by Russell et al [1974], Gonzalez and Tsurutani [1987], and Gonzalez et al [1994]. The papers mentioned above analyzed the duration of the southward IMF Bz component which is enough to generate magnetic storms, but the duration of the main phase was studied less intensively and it was shown that the duration of the main phase may be from 2 h to 1 day [see, e.g., Yokoyama and Kamide, 1997;Vieira et al, 2004;Vichare et al, 2005;Gonzalez and Echer, 2005;Yermolaev et al, 2007aYermolaev et al, , 2007bHutchinson et al, 2011;Nikolaeva et al, 2012, and Though it is well known that the dynamics of magnetic storms depends on the type of interplanetary drivers (see, e.g., papers by Borovsky and Denton [2006], Yermolaev et al [2010Yermolaev et al [ , 2012a, Guo et al [2011], Liemohn and Katus [2012], Nikolaeva et al [2013], Cramer et al [2013], and references therein), the majority of previous works have not made a selection by types of solar wind streams which generated the storms. In other works, the selection was either performed only for a limited type of solar wind or for a complex of types.…”
Section: Introductionmentioning
confidence: 99%
“…While it is known that the most extensive aurorae (and the strongest auroral electrojets and ground disturbances) are caused by CMEs [Borovsky and Denton, 2006], HSSs dominate the auroral activity over long time scales. Tanskanen et al [2005] studied substorms using ground-based magnetograms and found that their yearly averaged occurrences and amplitudes over the solar cycle strongly correlate with the annual means of the solar wind speed dominated by high-speed streams.…”
Section: 1002/2014ja019958mentioning
confidence: 99%
“…8 (Borovsky and Denton 2009). The CIRs seldom have fast shocks or continuous, strongly southward interplanetary magnetic field (IMF) and thus drive only moderate geomagnetic activity (Scholer 1999;Alves et al 2006;Borovsky and Denton 2006). It is generally believed that geomagnetic disturbances recurring at 27 day intervals could be associated with CIRs.…”
Section: Solar Windmentioning
confidence: 99%
“…Geomagnetic storms during the later declining and minimum phases of the solar cycle are caused mostly by CIRs whereas intense storms at solar maximum and the early declining phases of the cycle are caused by ICMEs (Cid et al 2004;Denton et al 2006). Borovsky and Denton (2006) have listed significant differences between CME driven and CIR driven storms and their effects on space-borne and ground based technological systems. They have also discussed the influence of storms on magnetospheric convection and energetic charged particle fluxes.…”
Section: Predictability Of Space Weathermentioning
confidence: 99%